Aedes aegypti abundance and insecticide resistance profiles in the Applying Wolbachia to Eliminate Dengue trial - Tantowijoyo, Warsito; Tanamas, Stephanie K.; Nurhayati, Indah; Setyawan, Sigit; Budiwati, Nida; Fitriana, Iva; Ernesia, Inggrid; Wardana, Dwi Satria; Supriyati, Endah; Arguni, Eggi; Meitika, Yeti; Prabowo, Equatori; et al. (PLOS, 2022)
The Applying Wolbachia to Eliminate Dengue (AWED) trial was a parallel cluster rando-mised trial that demonstrated Wolbachia (wMel) introgression into Ae. aegypti populations reduced dengue incidence. In this predefined substudy, we compared between treatment arms, the relative abundance of Ae. aegypti and Ae. albopictus before, during and after wMel-introgression. Between March 2015 and March 2020, 60,084 BG trap collections yielded 478,254 Ae. aegypti and 17,623 Ae. albopictus. Between treatment arms there was no measurable difference in Ae. aegypti relative abundance before or after wMel-deploy-ments, with a count ratio of 0.96 (95% CI 0.76, 1.21) and 1.00 (95% CI 0.85, 1.17) respectively. More Ae. aegypti were caught per trap per week in the wMel-intervention arm compared to the control arm during wMel deployments (count ratio 1.23 (95% CI 1.03, 1.46)). Between treatment arms there was no measurable difference in the Ae. albopictus population size before, during or after wMel-deployment (overall count ratio 1.10 (95% CI 0.89, 1.35)). We also compared insecticide resistance phenotypes of Ae. aegypti in the first and second years after wMel-deployments. Ae. aegypti field populations from wMel-treated and untreated arms were similarly resistant to malathion (0.8%), permethrin (1.25%) and cyfluthrin (0.15%) in year 1 and year 2 of the trial. In summary, we found no between-arm differences in the relative abundance of Ae. aegypti or Ae. albopictus prior to or after wMel introgression, and no between-arm difference in Ae. aegypti insecticide resistance phenotypes. These data suggest neither Aedes abundance, nor insecticide resistance, confounded the epidemiological outcomes of the AWED trial.